MODEL BANGKITAN DAN TARIKAN PERGERAKAN KAWASAN PERMUKIMAN DI BANDARLAMPUNG - Canggah Abiyyu Ali'in Saputri; Aleksander Purba; Shahnaz Nabila Fuady (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2021)
Urban planning is a solution to problems that may arise as a result of the continued increase in the population of the city which is also associated with a variety of activities which then affect land use and urban mobility, these causing transportation problems to be identified at this time so that preventive actions can be planned for the future. In Bandarlampung as a Metropolitan City, it can be seen that the population is increasingly dense and its activities are increasingly diverse as seen on Jalan Urip Sumoharjo, which is surrounded by heterogeneous land uses like residential areas, trade and service areas and public service areas where Jalan Urip Sumoharjo is a strategic road for in Bandarlampung. So the purpose of this research are to identify the model of trip generation and trip attraction that determine the factors causing the movement of residential area of Jalan Urip Sumoharjo. The research method used are multiple linear regression and descriptive statistical analysis. Based on the analysis result, the factors that influence movement on Jalan Urip Sumoharjo are family members, number of working family members, average distance and time of movement, monthly income, vehicle ownership, purpose and travel destination, and accessibility.